Genetic effects of traits associated to nitrogen use efficiency in maize - DoVale, Júlio César; Fritsche‑Neto, Roberto; Bermudez, Felipe; Miranda, Glauco Vieira (Pesquisa Agropecuaria Brasileira, 2012)
The objectives of this work were to determine the genetic control of nitrogen use efficiency (NUE), to identify the importance of N acquisition (NAE) and utilization (NUtE) efficiencies on its composition, and to quantify the relation between production of shoot (SDM) and root dry matter mass with NUE and its components. Forty‑one hybrid combinations were evaluated in two N availabilities: low (LN) and high (HN). A randomized complete block design with two replicates, in a simple factorial arrangement (hybrid combination x N availability), was used. Statistical analyses were done using mixed model equations. High magnitude correlations were detected between NAE and NUE, and between these efficiencies and SDM in LN and HN. In both N availabilities, additive genetic effects were more important for the traits associated with NUE. Therefore, selection based on the individual performance of inbred lines as to SDM can allow for the obtainment of genotypes with high NUE. Independently of N availability, NAE is the most important component of NUE.